Does Entrepreneurship Capital Matter? - Audretsch, David B.; Keilbach, Max (Entrepreneurship Theory and Practice, 2004)
Economics has identified three types of capital as the drivers of economic growth—physical capital, human capital, and knowledge capital. This article introduces the concept of entrepreneurship capital and suggests that it is also an important factor shaping the economic performance of an economy. We define entrepreneurship capital as those factors influencing and shaping an economy's milieu of agents in such a way as to be conducive to the creation of new firms. The hypothesis that entrepreneurship capital is positively linked to economic growth is then tested by examining the relationship between several different measures of entrepreneurship capital and regional economic performance, measured as per–capita income for Germany. The empirical evidence suggests that there is indeed a positive link between entrepreneurship capital and regional economic performance. These results suggest a new direction for public policy that focuses on instruments to enhance entrepreneurship capital.